PENGARUH MOTIVASI INTRINSIK, MOTIVASI EKSTRINSIK DAN KEPEMIMPINAN TRANSFORMASIONAL TERHADAP PRODUKTIVITAS KERJA PEGAWAI DI BIDANG PENGELOLAAN PERSAMPAHAN PADA DINAS LINGKUNGAN HIDUP KOTA BATAM - Lamra Megawati Br Sipayung; Ramon Zamora (BENING, 2017)
The purposes of this research, were to know the influence of intrinsic motivation, extrinsic motivation and transformational leadership on employee productivity in the Field of Waste Management at the Department of the Environment Batam. The population in this study were all employees in the Field of Waste Management. Samples taken as many as 45 respondents using total sampling technique. Based on the research results, obtained the following regression equation: Y = 1.596 + 0.805 X1 + 0.618 X2 + (-0.471) X4. Based on statistical data analysis, indicators in this study are valid and are reliable variables. In the classic assumption test, regression model multicoloniarity free does not occur heteroskedastisitas, and normal distribution. The sequence individually on each of the most influential variable is the variable with the intrinsic motivation and extrinsic motivation with thitung of 8.171 with thitung of 4.045, while the transformational leadership variable has no effect on employee productivity because ttable (2,019) greater than thitung (-2.751). Simultaneously intrinsic motivation, extrinsic motivation and transformational leadership positively affect work productivity.